Paradigm shifts in macrosociology - Renate Mayntz (Max Planck Institute for the Study of Societies, 2023)
This paper looks at changes in macrosociological paradigms for social development that traditionally stretch from the primitive society through the stratified medieval society to the image of a functionally differentiated modern society. Changing the perspective from a systems theoretical view of societies to an actor perspective, I focus on populations of individual actors and organizations as collective actors. Over recent decades, important structural changes in the nature of populations and of organizations have taken place in the Western world. The most important relate to economic globalization and financial internationalization. An increasingly flexible population and narrowly goal-specific organizations produce a situation of societal instability that appears to characterize the present, though its causes reach back half a century. – – Dieser Aufsatz betrachtet Veränderungen in makrosoziologischen Gesellschaftsvorstellungen, die traditionell von der primitiven über die mittelalterlich geschichtete Gesellschaft zur funktionell differenzierten modernen Gesellschaft führen. Verändert man die systemtheoretische zu einer akteurtheoretischen Perspektive, die mit Populationen individueller Akteure und Organisationen als kollektiven Akteuren arbeitet, werden wichtige strukturelle Veränderungen in westlichen Gesellschaften sichtbar. Die wichtigsten Veränderungen betreffen die ökonomische Globalisierung und die finanzielle Internationalisierung. Eine zunehmend flexibel agierende Population individueller Akteure und auf eng definierte Ziele orientierte Organisationen führen zu einer Situation, die heute als Instabilität wahrgenommen wird, obwohl ihre Ursachen über ein halbes Jahrhundert zurück reichen.
hdl:21.11116/0000-000D-4EFC-1
Keywords: 300; Integrationsbias der Systemtheorie; Konfliktlinien in gegenwärtigen Gesellschaften; Systemzerfall und seine Ursachen; conflict lines in present societies; integration bias of systems theory; system decomposition and its sources